Infra-Low Frequency Neurofeedback in the Treatment of Patients With Chronic Eating Disorder and Comorbid Post-Traumatic Stress Disorder - Winkeler, Anna; Winkeler, Markus; Imgart, Hartmut (Frontiers in Human Neuroscience, 2022)
The treatment of patients suffering from an eating disorder and a comorbid post-traumatic stress disorder is challenging and often leads to poor outcomes. In a randomized control trial, we evaluated to what extent adding Infra-Low Frequency (ILF) neurofeedback could improve symptom reduction within an established inpatient treatment program. In a randomized two-group design, patients suffering from an eating disorder (anorexia nervosa, bulimia nervosa, or binge eating disorder) and comorbid post-traumatic stress disorder (N=36) were examined while attending an in-patient treatment program in a clinic for psychosomatic disorders. The intervention group received ILF neurofeedback in addition to regular therapy, while the control group received “media-supported relaxation” as a placebo intervention. At the beginning and at the end of their treatment, all participants completed the Eating Disorder Examination-Questionnaire (EDE-Q) as a measure of eating disorder psychopathology and the Impact of Event Scale-Revised (IES-R) in order to assess symptoms of post-traumatic stress. Changes in EDE-Q and IES-R scores over time served as primary outcomes as well as increase of body mass index in underweight patients. Secondary outcomes were the perceived benefit of the received intervention, global assessment of psychological treatment success, and complications in the course of treatment. Statistical evaluation was carried out with repeated measurement analysis of variance for the primary outcomes and with t-tests and Fisher’s exact test for the secondary outcomes. Our results indicate better treatment outcomes in the ILF neurofeedback group with regard to trauma-associated avoidance as well as with regard to restraint eating and increase of body weight. Furthermore, patients who had received ILF neurofeedback rated the intervention they received and, in tendency, their overall treatment more positively and they experienced fewer complications in the course of treatment. ILF neurofeedback is very well accepted by patients and seems to provide a relevant additional benefit in some aspects of symptom reduction. Findings confirm the feasibility of embedding this treatment approach in an inpatient setting and support the case for a larger study for greater statistical power.